'I (really) know what you mean'. Mechanisms of experiential peer support for young people with criminal behavior: a qualitative study. Issue 5 (20th October 2021) - Lenkens, Margriet; Nagelhout, Gera E.; Schenk, Loïs; Sentse, Miranda; Severiens, Sabine; Engbersen, Godfried; Dijkhoff, Lisa; van Lenthe, Frank J.
ABSTRACT: Individuals with a criminal background are increasingly involved in support for people with criminal behavior. However, research into what happens in the relationship between these experiential peers (EPs) and clients is scarce. This qualitative study investigates EPs' perspectives on the mechanisms of experiential peer support and how this compares to regular support by care providers without lived experiences. We interviewed seventeen EPs who provided support to young people with criminal behavior. The results suggest that shared experiences between EPs and their clients play a central role. EPs identify with their clients, leading to empathy and a non-judgmental attitude. Clients seem to perceive EPs as credible role models who offer hope. EPs' lived experiences seem to induce a realistic view of desistance and an emphasis on a humane relationship with their client, which is characterized by equality, reciprocity, trust and sincerity. This recovery-oriented approach towards criminal behavior and desistance could also be utilized by non-EPs. Future research should investigate others' perspectives on and experiences with experiential peer support, in particular those of clients and co-workers.